N6-Methyladenosine Modification and Its Regulation of Respiratory Viruses - Feng, Qianyu; Zhao, Hongwei; Xu, Lili; Xie, Zhengde (Frontiers in Cell and Developmental Biology, 2021)
N6-methyladenosine (m6A) is a ubiquitous RNA modification in eukaryotes. It plays important roles in the translocation, stabilization and translation of mRNA. Many recent studies have shown that the dysregulation of m6A modification is connected with diseases caused by pathogenic viruses, and studies on the role of m6A in virus-host interactions have shown that m6A plays a wide range of regulatory roles in the life cycle of viruses. Respiratory viruses are common pathogens that can impose a large disease burden on young children and elderly people. Here, we review the effects of m6A modification on respiratory virus replication and life cycle and host immunity against viruses.